(untitled) (Philological Studies, 2019)
This article is devoted to the problem of interference in closely related languages. We research the phenomena of the Russian-Macedonian interference in texts of students-philologists. The artificial bilingualism is the greatest interest represents studying of cases of interference in closely related languages because seeming similarity of language systems brings to loss of control and speaking operates with units of the native language at text creation in a foreign language more freely. The material showed that the mistakes caused by interference at initial level of studying of language, meet at all levels of language system.